Persepsi Masyarakat Kelurahan Lenteng Agung terhadap Fungsi Taman Lenteng Agung Pingkal Sebagai Ruang Terbuka Hijau Publik - Yanuar Dwi Ananto; Ilham Badaruddin Mataburu; Fauzi Ramadhoan A’Rachman (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
This study aims to determine the public's perception of the function of Lenteng Agung Pingkal Park as public green open space so that it can be an evaluation material for optimizing green open spaces. The research method used is a descriptive method. The analysis was conducted using a quantitative approach, used to identify the function of the Lenteng Agung Pingkal Park based on community perceptions using scoring. Measurement of perceptions and social conditions of society is measured using a Likert scale. The sampling technique is a purposive sample. Population and sample used were the people of Lenteng Agung Village who visited Lenteng Agung Pingkal Park, and the sample used was the productive age community (RW) 07, 08, 09 which was 15 to 64 years old. Collecting data using observation, questionnaires, and documentation. The variable function of Taman Lenteng Agung as a green open space includes socio-cultural, aesthetic, and economic functions. The results this study that the public's perception of the functions in socio-cultural, aesthetic, and economic overall of Lenteng Agung Pingkal Park included the good category with a score of 4.094. This proves that the government and park management are considered to be good at organizing public green open spaces.